Diagnosis, Prevention and Treatment of Chronic Catarrhal Gingivitis in Children - Ganiev J. I; Xabibova N. N. (International Journal on Integrated Education, 2021)
The article discusses in more detail the purpose and content of the EUMC structural components by the example of the manual on the discipline "Computer Science Information Technology" for students enrolled in the specialty of ekonomiki and religious studies